2011
DOI: 10.1155/2011/285346
|View full text |Cite
|
Sign up to set email alerts
|

Caustics, Cold Flows, and Annual Modulation

Aravind Natarajan

Abstract: We discuss the formation of dark matter caustics, and their possible detection by future dark matter experiments. The annual modulation expected in the recoil rate measured by a dark matter detector is discussed. We consider the example of dark matter particles with a Maxwell-Boltzmann velocity distribution modified by a cold stream due to a nearby caustic. It is shown that the effect of the caustic flow is potentially detectable, even when the density enhancement due to the caustic is small. This makes the an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Reconstructing the stream parameters for arbitrary dark matter streams using a combination of the percentage modulation and the total number of recoils will enable us to understand the phase space distribution of dark matter in the solar neighborhood. In previous work [3,4], we showed that streams can alter the phase and structure of the annual modulation. In certain energy bins, the presence of the stream may only be apparent during part of the year, when the stream speed relative to the earth is largest.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Reconstructing the stream parameters for arbitrary dark matter streams using a combination of the percentage modulation and the total number of recoils will enable us to understand the phase space distribution of dark matter in the solar neighborhood. In previous work [3,4], we showed that streams can alter the phase and structure of the annual modulation. In certain energy bins, the presence of the stream may only be apparent during part of the year, when the stream speed relative to the earth is largest.…”
Section: Discussionmentioning
confidence: 87%
“…For sufficiently large exposures, the annual modulation provides additional information. The annual modulation is an excellent indicator of streams [3,4], and should reveal the presence of the stream at a measured energy near the cutoff energy of the stream. Reconstructing the stream parameters for arbitrary dark matter streams using a combination of the percentage modulation and the total number of recoils will enable us to understand the phase space distribution of dark matter in the solar neighborhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such flows are predicted, for example, by models of late infall of non-virialized DM into the the Galactic halo. These streams will typically have much smaller velocity dispersion than the virialized DM [27][28][29].…”
Section: Jcap06(2014)059mentioning
confidence: 99%
“…The existence of caustics is relevant to the DAMA experiment since the velocity distribution in the vicinity of a dark matter inner caustic is dominated by the cold flow forming the caustic. In [29], the effect of the dominant flow of the self similar model on the annual modulation signature was calculated. The effect of other cold streams on the recoil rate has been discussed by several authors (see for example [30][31][32][33][34] [14,35] (In [14], a value of ξ = 0.733 is adopted).…”
Section: A Discrete Flows and Causticsmentioning
confidence: 99%